2021
DOI: 10.14201/scero202152e1136
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la Covid-19 en las personas con discapacidades intelectuales y del desarrollo, sus familiares y los profesionales y organizaciones de apoyo

Abstract: Nuestro mundo se ha visto transformado por el coronavirus y la infección que provoca. La gravedad de la enfermedad y las consecuencias del estado de alarma no afectan a todos por igual, siendo las personas con discapacidad intelectual y del desarrollo uno de los colectivos más vulnerables. El INICO y Plena inclusión realizaron un estudio con la finalidad de analizar el impacto de la COVID-19 y el confinamiento durante la primera ola en 2020 en las personas con discapacidad intelectual y del desarrollo, sus fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
1
1
Order By: Relevance
“…Paradoxically, however, our study results suggest that the mental health of PID who were confined to their residential center (not within the family unit) improved at this time. This contrasts with other studies of PID, which reported high rates of depression, anxiety, psychological distress, and loneliness during the early stages of the COVID-19 pandemic [6].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Paradoxically, however, our study results suggest that the mental health of PID who were confined to their residential center (not within the family unit) improved at this time. This contrasts with other studies of PID, which reported high rates of depression, anxiety, psychological distress, and loneliness during the early stages of the COVID-19 pandemic [6].…”
Section: Discussioncontrasting
confidence: 99%
“…This increase in needs, coupled with the loss of support staff due to infections and quarantines [ 48 ], may explain the relatively low levels of quality of life indicated by their scores [ 13 ]. As indicated in a study conducted by Crespo [ 6 ], the situation brought about by COVID-19 has highlighted the need to increase the number of professionals to provide better support to PID.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aunado a la ruptura social, la pandemia ha sido percibida por las personas con DCA y sus familiares entrevistados como un factor agravante a la condición de rezago ya pre-existente, no sólo por un aspecto de vulnerabilidad ante el contagio, sino también por el desplazamiento de sus necesidades a un lugar inferior dentro del elenco de las prioridades sanitarias (Crespo Cuadrado et al, 2021). En los relatos, esto parece traducirse en una mayor desconfianza en el sistema.…”
Section: Resignificación Personal Y Socialunclassified